2015
DOI: 10.1091/mbc.e14-02-0734
|View full text |Cite
|
Sign up to set email alerts
|

Functional insight into the role of Orc6 in septin complex filament formation inDrosophila

Abstract: Detailed roles of conserved septin motifs, GTP, and Orc6 in Drosophila septin complex functions are examined both in vitro and in vivo in a live animal. A novel mechanism of Orc6 regulation of septin filament formation is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 69 publications
(154 reference statements)
1
25
0
Order By: Relevance
“…The metazoan Orc6 consists of two domains, a larger N‐terminal domain which carries homology with TFIIB transcription factor and is important for DNA binding [Chesnokov et al, ; Balasov et al, ; Liu et al, ] and a shorter C‐terminal domain important for the function of Orc6 in cytokinesis [Prasanth et al, ; Chesnokov et al, ; Huijbregts et al, ; Bernal and Venkitaraman, ; Akhmetova et al, ]. The C‐terminal domain of Orc6 is also essential and sufficient for the interaction of Orc6 with core ORC [Bleichert et al, ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metazoan Orc6 consists of two domains, a larger N‐terminal domain which carries homology with TFIIB transcription factor and is important for DNA binding [Chesnokov et al, ; Balasov et al, ; Liu et al, ] and a shorter C‐terminal domain important for the function of Orc6 in cytokinesis [Prasanth et al, ; Chesnokov et al, ; Huijbregts et al, ; Bernal and Venkitaraman, ; Akhmetova et al, ]. The C‐terminal domain of Orc6 is also essential and sufficient for the interaction of Orc6 with core ORC [Bleichert et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Orc6 is also essential for cytokinesis in Drosophila and human cells [Prasanth et al, ; Chesnokov et al, ]. In Drosophila , Orc6 stimulates septin complex GTPase activity and polymerization during filament assembly through protein–protein interactions [Huijbregts et al, ; Akhmetova et al, ]. Metazoan Orc6 proteins consist of two functional domains: a larger N‐terminal domain important for binding of DNA and smaller C‐terminal domain important for protein‐protein interactions [Chesnokov et al, ; Balasov et al, ; Duncker et al, ; Bleichert et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of SEPT7 destabilizes other core septins and prevents the formation of functional filaments. Although most of the septins, except the SEPT6 family, display intrinsic GTPase activity, nucleotide binding rather than GTPase activity has been implicated in septin filament formation (Versele and Thorner, 2004;Sirajuddin et al, 2009;Akhmetova et al, 2015). In addition, association of septins with membrane lipids and other cytoskeletal elements can influence filament formation (Kinoshita et al, 2002;Tanaka-Takiguchi et al, 2009;Bertin et al, 2010).…”
Section: Septin-independent Cytokinesis In Invertebrate Modelsmentioning
confidence: 99%
“…Besides that, it was demonstrated that the C-terminal domain contains a motif which mediates an ORC6 interaction with the Pnut protein, a component of the septin complex [20]. ORC6 promotes septin polymerization due to its ability to form a dimer [102,103]. Although the molecular mechanism for the septin filament assembly still remains poorly understood, the results obtained so far provide strong evidence for the direct involvement of ORC6 in this process.…”
Section: Centrosome Duplication and Cytokinesismentioning
confidence: 99%